Statutory Compliance at Prescription of Medications with Restrictions to Use in Gestation and Lactation Periods - Polina G. Gabay; Vasiliy V. Orlenko (Вопросы современной педиатрии, 2019)
Some medication instructions have records about the need of caution in case of management in pregnant women or during lactation period. Moreover the instructions do not have direct prohibition against drug administration during gestation and lactation periods. In this regard the legitimacy of such medications prescription to pregnant women or women during lactation period is questionable (even when physician thinks that there are indications for such therapy). Another question is legal responsibility of the physician in case of any adverse effects development. The evidence favouring legitimacy of physician actions on prescribing such medication are considered as well as the probability of physician prosecution to civil and criminal liability are analyzed in this article. Special attention should be given to the issue of recognition of physician actions as reasonable risk. The guidelines based on performed analysis have been developed. The implementation of this guidelines can significantly reduce the risks of physician legal exposure.